Implementasi Penggunaan Program Autodesk Revit pada Pekerjaan Struktur Proyek Pembangunan Gereja Bethany Yestoya Malang - Dimas Febrianto Pratama; Michella Beatrix, Michella Beatrix (Jurnal Kridatama Sains dan Teknologi, 2024)
In a construction project, the planner, owner, supervisor, and project implementer have a joint task, namely to complete a project quickly, effectively, and efficiently. However, the larger the project implemented, the more complex the problems that occur. One of the problems that often occurs is the problem related to the amount of work volume. To overcome these problems, a concept called Building Information Modelling (BIM) is used. BIM can do modeling in 2D and 3D which is used to obtain the resulting drawings/working drawings and the necessary building dimensions. This study uses primary and secondary data from the project location in the form of general project data, work drawings/shopdrawings, and structural work Bill Of Quantity which are processed using the BIM program, namely Autodesk Revit, with the help of another computing program Microsoft Excel. The results of this study indicate that the calculation of the total volume between the Autodesk Revit program and the conventional method has a difference of 436.85 m3 in concrete work and 168481.22 kg in rebar work